The Stranger - Coben, Harlan, 1962- (London Orion Books, 2015)
The Sunday Times number one bestselling author delivers a shocking thriller that proves that a well-placed lie can help build a comfortable life - and a secret has the same explosive power to destroy it
Keywords: Married people -- Conspiracies -- Suspense fiction